Primary Management in General, Vascular and Thoracic Surgery A Practical Approach - Bissacco, Daniele; Settembrini, Alberto M.; Mazzari, Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
(3z(BThinking as a specialist, acting as an ER doctor(3y (BThe emergency setting remains one of the most important parts of daily clinical practice for surgeons. Moreover, the triage surgeon may be faced with complicated patients, who are often suffering from a wide range of diseases and emerging conditions. To this end, the emergency surgeon must know how to interpret the symptoms/signs of each condition and initiate appropriate management before directing the patient to the most correct path and specialist. Although several books have been published concerning a specific surgical field (e.g. emergencies in vascular, thoracic or general surgery), this book provides a concise and quick point of view describing the clinical and instrumental surgical pictures in all vascular, thoracic, and general surgical emergencies. This approach can be useful in gaining a practical understanding of different clinical scenarios in order to adopt a correct management and treatment. It offers a simple guide to discriminating between urgent and non-urgent conditions, avoiding unnecessary diagnostic and interventional workup. This book would like to be a practical help also for general practitioners and emergency physicians to learn more about primary management of life threatening pathologies.s
1 HISTORICAL OVERVIEW -- I SURGICAL INSTRUMENTS AND MATERIALS -- 2 Surgical instruments and materials in General Surgery -- 3 Surgical instruments and materials in Thoracic Surgery -- 4 Surgical instruments and materials in Vascular Surgery -- II NECK -- 5 Neck: surgical anatomy and general consideration in emergency settings -- 6 Supra-aortic trunks emergency conditions -- 7 Upper airways tract in emergency settings -- 8 Thyroid and parathyroids for general surgeons -- 9 Multidisciplinary surgical consensus on neck emergencies -- III CHEST -- 10 Chest: surgical anatomy and general consideration in emergency settings -- 11 Acute aortic syndromes.-12 Pulmonary and thoracic emergencies -- 13 Upper gastrointestinal tract acute conditions -- 14 Multidisciplinary surgical consensus on chest emergencies. IV ABDOMEN -- 15 Abdomen: surgical anatomy and general consideration in emergency settings -- 16 Acute abdominal aorta and visceral vessel disease -- 17 Acute abdomen and acute abdominal conditions -- 18 Multidisciplinary surgical consensus on abdominal emergencies -- V UPPER AND LOWER LIMBS -- 19 Upper and lower limbs: surgical anatomy and general consideration in emergency settings -- 20 Acute and chronic limb ischemia -- 21 Non-ischemic acute conditions of limbs -- 22 Multidisciplinary surgical consensus on limbs emergencies -- VI SPECIFIC CLINICAL PICTURES: SURGEON PERSPECTIVES -- 23 The infected and septic patient.
Keywords: Blood-vessels$1 (BSurgery.s; Surgery; Diseases; Medical care; Vascular Surgery; Surgery; Diseases; Health Care; Surgical Procedures, Operative